Classroom note: An inductive derivation of Stirling numbers of the second kind and their applications in statistics. Issue 2 (1997) - Joarder, Anwar H.; Mahmood, Munir
Abstract : An inductive method has been presented for finding Stirling numbers of the second kind. Applications to some discrete probability distributions for finding higher order moments have been discussed.